A critical look to the adaptive reuse of traditional urban houses in the Walled City of Nicosia. Issue 2 (3rd May 2016) - Mısırlısoy, D.; Günçe, K.
ABSTRACT: The preservation of traditional residential architecture is crucial since it is a prime indicator of the cultural relationships between it and its locality. Sustaining traditional residential architecture is important in terms of cultural continuity. The study questions the appropriateness of the new functions of heritage buildings through the evaluation of socio-cultural, economic and physical aspects of the adaptive reuse of traditional urban houses in the Walled City of Nicosia. The selected buildings were used as houses before and new functions have been assigned to them. This article aims to measure the success of the adaptive reuse projects by identifying the benefits gained from the adaptive reuse. As the data collection method of study, questionnaires were conducted with architects, who are registered and active members of the chamber in the northern sector of Cyprus. The findings show that traditional urban houses have been preserved physically but the buildings lack a living function due to the neglect of socio-cultural and economic aspects in the decision-making process.